2021
DOI: 10.19128/turje.814621
|View full text |Cite
|
Sign up to set email alerts
|

Depression-anxiety and coping strategies of adolescents during the Covid-19 pandemic

Abstract: The aim of the present study was to examine the levels of anxiety, depression and coping of adolescents during the Covid-19 pandemic. The study was carried out with 3058 students (2080 females, 978 males) who are continuing their secondary and high school educations at Şahinbey District of Gaziantep. Personal Information Form, The Revised Child Anxiety and Depression Scale -Child Version and Coping Scale for Children and Adolescents were used for data collection. Independent Samples t-Test and One-Way ANOVA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
(40 reference statements)
2
23
0
1
Order By: Relevance
“…Millions of students and teachers have tried to adapt to this new situation; however, teachers have mentioned being in significant need of in-service training and psychological support during this process [ 26 ]. The COVID-19 pandemic period was not considered easy for either teachers or their students, and students’ anxiety and stress levels reportedly increased during this troubling period [ 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Millions of students and teachers have tried to adapt to this new situation; however, teachers have mentioned being in significant need of in-service training and psychological support during this process [ 26 ]. The COVID-19 pandemic period was not considered easy for either teachers or their students, and students’ anxiety and stress levels reportedly increased during this troubling period [ 27 , 28 , 29 , 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For children living in Majority World 1 countries (MWC) (i.e. countries where the majority of the global population lives, also often referred to as Low‐ and Middle‐Income or Global South Countries), these challenges have been exacerbated by pre‐existing systemic inequalities (Kola et al, 2021 ; Nwosu & Oyenubi, 2021 ; Türk et al, 2021 ; Zar et al, 2020 ). Longer‐term negative repercussions may be more pronounced for these children, as inequalities are reinforced and further entrenched.…”
Section: Introductionmentioning
confidence: 99%
“…Major public health emergencies refer to the sudden occurrence of major infectious diseases, mass diseases of unknown origin, major food and occupational poisoning, and other events that may cause serious damage to the public health (Liu Y. Y. et al, 2020). Research has shown that anxiety and depression are the most common mental health problems that the general public can easily develop under the major public health emergencies (Loh et al, 2005;Motreff et al, 2020;Og et al, 2020;Türk et al, 2021).…”
Section: A Summary Of the Literaturementioning
confidence: 99%
“…Moreover, family is one of the most important environments for the development of adolescents' mental health (Tian and Li, 2005;Xie et al, 2008;Türk et al, 2021). The higher the degree of family dysfunction, the higher the levels of adolescents' anxiety and depression would be (Xie et al, 2008).…”
Section: A Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation